Community Perception of Biogas Production from Cacao Waste - Arumsari, Bernardia Vitri; Utami, Arini Wahyu; Harun, Mohd Razif (Agro Ekonomi, 2024)
Indonesia can use bioenergy to meet its renewable energy consumption target. Community perception must be known when designing communication strategies or policies regarding biogas as a renewable energy source. This study aims to 1) evaluate the knowledge, attitude, behavior, and overall perception of the Gambiran Hamlet, Gunungkidul, Yogyakarta, Indonesia residents on biogas from cacao waste, and 2) investigate the factors affecting the perception of the Gambiran Hamlet residents on biogas. Socio-economic data were collected by doing surveys and observation. One sample t-test was conducted to determine the perception of the Gambiran Hamlet community towards biogas made from cacao waste. Moreover, logistic regression was used to determine the factors affecting the perception of biogas. Most of the residents can define biogas properly. Moreover, the residents' attitude and behavior were positive regarding relative advantage, compatibility, complexity, and observability components. Gambiran Hamlet residents’ perception of biogas from cacao waste is positive. Furthermore, the higher the educational attainment and being male, the greater the chance of a positive perception of biogas. However, household size, age, and income are statistically insignificant. Furthermore, socialization, training, and mentoring are needed for biogas installation. This research successfully provides fresh insights into residents' perception of biogas from cacao waste and uncovers key factors, like gender and education, influencing their perception, offering valuable guidance for targeted policy and communication strategies.